Ex vivo-generated lymphoid progenitors encompass both T cell and innate lymphoid cell fates - Gaudeaux, Pierre; Paillet, Juliette; Abou Alezz, Monah; Moirangthem, Ranjita Devi; Cascione, Sara; Martin Corredera, Marta; Dolens, Anne-Catherine; De Mulder, Katrien; Velghe, Imke; Vandekerckhove, Bart; Lavaert, Marieke; Robil, Noémie; et al. (Frontiers in Immunology, 2025)
IntroductionWe previously established a feeder-free cell therapy platform for the ex vivo generation of lymphoid-primed progenitors using immobilized Delta-like ligand 4 (DLL4). In vivo studies demonstrated that adoptive transfer of these progenitors accelerates T cell reconstitution following thymic engraftment.MethodTo further explore the full therapeutic potential of this cell product, we performed a comprehensive molecular and phenotypic characterization using single cell RNA sequencing and mass cytometry analysis.ResultsOur analysis revealed the presence of distinct cell subsets within the cellular product characterized mainly by commitment to lymphoid lineages. Using integrated transcriptomic analyses to compare these ex vivo-generated progenitors to in vivo human thymocytes, we revealed strong similarities with early stages of T cell development, underscoring the physiological relevance of our system. We also delineated two distinct developmental trajectories within the CD7+ progenitor population: a T cell-oriented path, marked by CD5 upregulation, and an innate lymphoid cell (ILC)-oriented branch, identified by CD161 expression and an ILC-like gene signature. Despite these lineage predispositions, both subsets demonstrated plasticity, retaining the ability to differentiate into both T cells and natural killer (NK) cells in vitro. Additionally, in our experimental setting, we observed that BCL11B, a transcription factor essential for T cell commitment, regulates negatively myeloid cell differentiation while preserving the potential for NK cell development.ConclusionThese findings underscore the versatility of DLL4-based lymphoid progenitors in generating either T cells or ILCs in response to environmental cues. This research paves the way for innovative cell therapy approaches to treat immune deficiencies and cancer- and age-related immune dysfunctions.